Aerodynamics of electric cars in platoon SAGE publications. (April 2021) - Ebrahim, Hesham; Dominy, Robert; Martin, Nick
The potential aerodynamic benefits of operating full-scale electric vehicles in platoons of 2 and 3 vehicles have been investigated. Since drag reduction has a direct impact on vehicle range, power consumption was measured directly and surface pressure measurements were made to characterise the changes in pressure field that influence the power required to overcome aerodynamic drag. CFD simulations were validated against the track measurements to assess the limitations of using a practical, limited number of pressure tappings to measure drag. The overall power consumption for the whole platoon was found to reduce proportionally with the reduction of vehicle spacing and it was also observed that increasing the number of vehicles in the platoon from 2 to 3 further increased the power savings from 33.4% to 39.1%. These power savings were attributed primarily to changes in surface pressure acting on the base of the leading vehicle and the forebody of the trailing vehicle.